Non-volatile voltage-controlled magnetization in single-phase multiferroic ceramics at room temperature - Zimeng Hu; Gavin B.G. Stenning; Hangfeng Zhang; Yu Shi; Vladimir Koval; Wanting Hu; Zhiyong Zhou; Chenglong Jia; Isaac Abrahams; Haixue Yan (Journal of Materiomics)
Single-phase multiferroics (MFs) exhibiting ferroelectricity and ferromagnetism and the strong magnetoelectric (ME) coupling effect at room temperature are seen as key to the development of the next-generation of spintronic devices, multi-state memories, logic devices and sensors. Herein, the single-tetragonal phase (1–x) (Sr0·3Bi0·35Na0·329Li0.021)TiO3-xBiFeO3 (x = 0.2 or 0.4) system was designed to study the intrinsic ME coupling effect at room temperature and high frequencies. The polarization arises from the cooperative displacement of both Fe3+ and Ti4+ relative to the oxygen sublattice in the tetragonally distorted perovskite structure, and the magnetization stems from indirect exchange magnetic interaction between adjacent iron ions. A switchable voltage-controlled magnetization was confirmed by a change of the coercive magnetic field, Hc, and remnant magnetization, Mr, in the x = 0.4 component subjected to an external electric field at room temperature and was possibly attributed to a strain-mediated ME coupling effect. In addition, resonance behaviours of the complex magnetic permeability and complex dielectric permittivity in the GHz band indicate that this ME effect is intrinsic in nature and could broaden the applications of multiferroics to devices operating at microwave frequencies.